RESEARCH MODULE DEVELOPMENT OF ANIMAL TISSUE STRUCTURE AND FUNCTION - Ervina Dewi; Rahmi Agustina; Nasyta Irhamna; Yuswardi Yuswardi (Postgraduate, University of Mataram, 2023)
This study aims to produce teaching material products in the form of research-based modules that contain techniques and research results on animal tissue. The development model used as a reference in the development of this research-based module is the Thiagarajan (4D) development model which consists of the define, design, develop and disseminate stages, but the dissemination stage was not carried out in this study. The results of the module validation from material experts and media experts stated the level of validity of the module with a percentage of 81,17% with very good qualifications and the criteria are Valid/Not Revised and small group test 90,64% with very practical criteria to use. It can be concluded that the resulting structure and function research-based module of animal tissue is feasible to use because it has been validated